2020
DOI: 10.1186/s40461-020-00097-6
|View full text |Cite
|
Sign up to set email alerts
|

‘What do you mean by ethical compass?’ Bachelor students’ ideas about being a moral professional

Abstract: This article aims to explore the moral ideas and experiences that students at Dutch universities of applied sciences (UAS) have of being a professional with an ‘ethical compass.’ Semi-structured interviews were held with 36 fourth-year Bachelor students divided over four institutions and three different programmes: Initial Teacher Education, Business Services and Information and Communication Technology. Findings show that students say they strive to be(come) moral professionals, but that they have difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…In a previous empirical study, we presented the views of students from three different programmes: Initial Teacher Education (ITE), Business Services (BS), and Information and Communication Technology (ICT). These views included (1) the students' ideas about what it means to have an ethical compass, and (2) about the way in which their ethical compasses had been formed ( Van Stekelenburg et al 2020b). This article presents the analysis of ITE, BS and ICT students' responses to questions about their internship experiences in relation to the use of their ethical compasses.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous empirical study, we presented the views of students from three different programmes: Initial Teacher Education (ITE), Business Services (BS), and Information and Communication Technology (ICT). These views included (1) the students' ideas about what it means to have an ethical compass, and (2) about the way in which their ethical compasses had been formed ( Van Stekelenburg et al 2020b). This article presents the analysis of ITE, BS and ICT students' responses to questions about their internship experiences in relation to the use of their ethical compasses.…”
Section: Introductionmentioning
confidence: 99%
“…The concept value-expressive attitude offers specification because it concentrates on the person's psychological tendency. Their study showed that students associated ethical compass with "gut feeling" or intuition (van Stekelenburg, Smerecnik et al, 2020). Gut feeling and intuition are concepts from the affective domain and are therefore important factors associated with inward affective involvement.…”
Section: 0mentioning
confidence: 99%
“…The other influences range from hereditary/genetic factors (Baumrind, 1967;Dahl & Killen, 2018;Dworazik et al, 2019;Groenendyk & Volling, 2007;Neiderhiser et al, 2007;Ramos et al, 2019;Reiss et al, 2000;). Other environmental factors that influence morality development, and could affect the effect of parenting on ethical leadership development, include culture (Cowell & Decety, 2015;Martinez et al, 2020;Ramos et al, 2019), the effects of peers and influential figures in the society and education/schooling (Aquino & Reed, 2002;Brown & Trevino, 2014;Kalshoven et al, 2011;Seroussi & Yaffe, 2020;Van Stekelenburg, 2020). Early life experiences have also been shown to be a major determinant of the ethical disposition of a leader (Avolio et al, 2009;Brummelman et al, 2021;Montroy et al, 2016).…”
Section: Environmental Factors and Ethical Leadershipmentioning
confidence: 99%
“…Cowell and Decety (2015), Martinez et al (2020), and Ramos et al (2019) advance that environmental factors including culture influence the development of morality. Role models have also been shown to shape morality (Seroussi & Yaffe, 2020;Van Stekelenburg, 2020). It is noticeable that parenting can be attributed across all the possible influencers or factors of morality development.…”
Section: Introductionmentioning
confidence: 99%